(untitled) (Revista Venezolana de Salud Pública, 2018)
The Warao indigenous community in the Delta Amacuro state, Venezuela, without intending it, became historical internationally, when the English writer, Daniel Defoe, published in 1719, the adventures of Robinson Crusoe (autobiographical and fictional), considered the first English novel1; This pre-Columbian community, whose name comes from its own language: Wa, boat and Arao, people (canoe people), presented a series of public health needs (2-5) that motivated a diverse group of professionals, headed by the Doctors Raúl Arocha, Gerardo Sánchez, Gustavo Báez and Gloria Álvarez to place all their knowledge and skills in the solution of these diseases, is how the Non-Governmental Organization and apolitical "Na’Waraos" is created, which selects the population of Nabasanuka (Naba: pipe or river, and Sanuka: small) located at the geographic coordinates of LN 09 ° 08 ’11.9 "and LO 061 ° 03’31.2", to be the epicenter of the control of endemic and epidemic diseases of its inhabitants and others 30 nearby towns such as Wisidatu, Joarotu, Bajanarotu and Araguabici